Self-attitudes in the structure of motivational orientation of junior athletes - Popovych, I.; Savchuk, O.; Matusiak, H.; Kruglov, K.; Kryzhanovskyi, O.; Danko, D.; Huzar, V. (Journal of Physical Education and Sport, 2024)
The purpose of this study is to perform theoretical and empirical research on the role of self-attitude in shaping and developing the motivational orientation of junior athletes. Methods: The research sample consisted of junior male and female athletes aged 15-19 years (n = 82) (M = 17.22; SD = ±1.68; Me = 17). All participants trained at the sports schools "LSSCY Enerhetyk" in Lviv, Ukraine and "SSSYOR 1" in Ivano-Frankivsk, Ukraine. They represented individual sports such as freestyle wrestling, judo, Greco-Roman wrestling, track and field, and artistic gymnastics, as well as team sports including football and volleyball. To assess self-attitude, the "Methods of Studying Self-Attitude" (Panteleev, 1993) were used. The dimensions of motivational orientation were evaluated using the "Athlete`s Motivational Orientation" questionnaire (Smoldovskaya, 2022), and the relevant motives for juniors` sporting activities were identified through the "Motivation of Sports Activities" questionnaire (Fomenko & Lukova, 2021). Results. Twenty-five correlations, including nineteen direct correlations and six inverse correlations, were established. It was established that the most loaded parameters of juniors` self-attitudes are "self-acceptance" (SAc) with six correlations and "result-focused motivational orientation" (RsM) with seven correlations. Significant superiority of a high level of self-acceptance (Group 1) was determined by all the parameters of juniors` motivational orientation. It was emphasized that superiority by such parameters of self-attitude as "self-management" (U = 1656.50; = .031) and "self-acceptance" (U = 1448.00; <.001) testifies to the significance of self-management and self-acceptance for junior athletes. It was underscored that continuous negative emotions, even in juniors with high personal achievements, are capable of destroying sports success, which is indicated by the only significant superiority of Group 4 (low levels of RsM) by the parameter "self-blame" (U = 1502.00; <.001). Discussion and conclusions. It was substantiated that the research into the phenomenon of self-attitude in the structure of motivational orientation is the study of reflective characteristics of junior athletes` self-awareness aimed at achieving optimal sports results in training, competitive, and recovery activities. The development of reflective abilities, the improvement of self-regulation readiness and the formation of self-attitude have a direct correlation with motivational orientation, which can have a positive effect on performance in sporting activities. It was recommended that the obtained scientific results should be implemented in the educational and training process of sports schools for children and youth.